Nurses\' experiences when caring for abused children at the Georgetown Public Hospital Corporation - Goodridge, Shonette Stacy Crystal (2021)
Objective: Child abuse has major consequences on the child\'s psychological development. Healthcare workers play an intricate role in detecting and reporting child abuse. In most cases they are the first person to come into contact with abused children and therefore, are solely responsible to report this abuse immediately to the relevant authority. The objective of this study was to understand registered nurses\' experiences during the care of children who were victims of abuse at the public hospital in Guyana. Methods: This study was qualitative approach. Sixteen registered nurses who work in Georgetown Public Hospital cooperation (GPHC), Accident and Emergency Department (A&E), Intensive Care Unit (ICU) and Pediatric Department were interviewed individually. The study used a semi-structured interview questions as research tool, in order to allow freedom and spontaneity to the interviewee and capture the desired information. An interview guide (topic list) for interviews was prepared. The interview guide was, therefore, used to ensure that all relevant topics were covered. All interviews were recorded in audio files and then later transcribed by the authorized researcher. These interviews, transcribed by the researcher, provided useful input to the analytical process. The qualitative data was subjected to content analysis and thematic modality. Ethical approval was granted from the Ethical Review Committee, Ministry of Public Health, Guyana and the Georgetown Public Hospital Corporation, Medical & Professional Services, Research Committee. Results: The mean(±SD) age and clinical experience of the nurses were 30.1(±4.0), 8.4(±6.9) respectively. The nurses were aged between 25 and 55 and most of them had five to ten years of clinical experiences. The majority of nurses (87.5%) were female and 12.5% were male. Furthermore, 93.8% were Christian, 50.0% were single and 43.8% belong to Afro-Guyanese ethnic group. Most nurses (62.5%) in this study were station at the Accident & Emergency Department. Table 1 shows the demographic information of the participants. Five categories were organized from the analytical process, namely: 1. Types of Abuse; 2. Knowledge; 3. Aroused feelings; 4. Protocols and actions; 5. Suggested changes. The nurses feared the consequences for the child and the family and most nurses were emotionally taken away with the depth of child abuse although they had varying experiences with the abused children\'s family; most nurses mentioned the family being irresponsible. Many nurses pointed out the gaps and flaws in the abused child treatment at the hospital. All the nurses felt the need to improve the abused child care while at the hospital. Education, awareness and training were some of the suggestions mentioned to better manage the affected child. Conclusion: Registered nurses demonstrated gaps in knowledge and awareness of child abuse, due to their limited experience and training. Training stands out to be most crucial in improving documentation of such victims and to provide appropriate care to those victims. Nurses go through various emotional feelings as they care for child abuse victims. Therefore, it is necessary to implement support strategies that look to emphasis on support for the professionals. The nurses need training, counselling and experience to properly manage all of the complexity that exists in the situation of violence against children. Nurses are the first health care provider to deal with an abused child, therefore it\'s important to have awareness, responsibility and education to encounter child abuse cases.